Evaluation of rheumatoid arthritis-associated interstitial lung disease in patients treated with JAK inhibitors: a MAJIK-SFR cohort study - Adeline Ruyssen-Witrand; Jacques-Eric Gottenberg; Philippe Dieude; Rene-Marc Flipo; Jerome Avouac; Emanuelle Dernis; Anne Tournadre; Marie-Elise Truchetet; Raphaele Seror; André Ramon; Nicolas Roux; André Basch; et al. (RMD Open)
Objective To examine the course of interstitial lung disease associated with rheumatoid arthritis (RA-ILD) in France on treatment with Janus kinase inhibitors (JAKis) using the MAJIK-SFR registry.Methods Prospective national multicentre observational study identifying patients with RA-ILD from the MAJIK-SFR registry. Pulmonary assessment data were collected at JAKi initiation and follow-up visits (6 months, 12 months and a median of 21 months postinclusion), including chest high-resolution CT (HRCT), pulmonary function tests (forced vital capacity (FVC) and diffusing capacity of the lungs for carbon monoxide (DLCO)), acute exacerbations of ILD, respiratory infections and lung cancers.Results We enrolled 42 patients (26 women, 62%) with RA-ILD with a mean age of 61±13 years and a mean disease duration of 16±10 years. Compared with the 778 RA patients without ILD from the MAJIK registry, RA-ILD patients were older, displayed more severe and active disease and had more prevalent comorbidities. Non-specific interstitial pneumonia and usual interstitial pneumonia accounted for 46% and 43% of the chest HRCT ILD patterns, respectively. No significant changes in FVC and DLCO were observed during the follow-up period. Chest HRCT lesions remained stable in 69% of patients. Progressive ILD was identified in 8 patients (19%). 16 (38%) respiratory tract infections were observed. Only one acute regressive exacerbation of ILD was noted, and no lung cancer was diagnosed. No deaths occurred. JAKi was discontinued in 17 patients including 8 for inefficacy on joint involvement and 5 for intolerance.Conclusion The analysis indicates stability of RA-ILD in patients treated with JAKi. The tolerance profile of JAKi in this higher risk population did not reveal new safety signal.